Biological control of major postharvest fungal diseases of apple using two Lamiaceae extracts. (14th December 2022) - Cherrate, Mustapha; Echchgadda, Ghizlane; Amiri, Said; Ezrari, Said; Radouane, Nabil; Oulad El Majdoub, Yassine; El Hamss, Hajar; Maissour, Abdellah; Makroum, Kacem; Cacciola, Francesco; Lahlali, Rachid
Abstract: This study aimed to evaluate the antifungal activity of the aqueous extracts of two wild Lamiaceae species against P. expansum and B. cinerea and the impact of these treatments on fruit quality parameters. The in vitro results showed significant effect of the two aqueous extracts on both fungi mycelial growth. A. alpinus exhibited high antifungal efficacy against P. expansum with an inhibition rate ranging from 34.32 to 90.76% whereas T. vulgaris exhibit an inhibition rate against B. cinerea ranging from 61.87 to 97.94%. These results indicated that A. alpinus and T. vulgaris were extremely potent against both pathogens with an EC50 ranging from 0.82 to 2.39%. The in vivo experiments on apple fruit were very promising with an approximate efficacy varying from 64 to 79% with no impacts on fruit quality parameters. These results provide evidence that both plant species are an effective alternative to control postharvest diseases of fruit.